2016
DOI: 10.3109/13880209.2015.1113992
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals from Dodonaea viscosa and their antioxidant and anticholinesterase activities with structure–activity relationships

Abstract: Context Dodonaea viscosa (L.) Jacq (Sapindaceae) has been used in traditional medicine as antimalarial, antidiabetic and antibacterial agent, but further investigations are needed. Objective This study determines the antioxidant and anticholinesterase activities of six compounds (1-6) and two crystals (1A and 3A) isolated from D. viscosa, and discusses their structure-activity relationships. Materials and methods Antioxidant activity was evaluated using six complementary tests, i.e., b-carotene-linoleic acid; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…In their study of the structure–activity relationships, Muhammad et al. ( 2016 ) showed that the position of –OH and –OCH 3 has a great influence on the antioxidant activity.…”
Section: Resultsmentioning
confidence: 99%
“…In their study of the structure–activity relationships, Muhammad et al. ( 2016 ) showed that the position of –OH and –OCH 3 has a great influence on the antioxidant activity.…”
Section: Resultsmentioning
confidence: 99%
“…The results are tabulated in Table 3. It is a well-accepted notion that the presence and position of -OH groups in a molecule can increase or decrease the antioxidant activity [50]. Among diterpenes, compound 1 showed moderate activity which may be due to the presence of three exocyclic double bonds.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…54 The use of antioxidants may reduce the Alzheimer's disease progression and minimize the neuronal degeneration by inhibition of the acetylcholinesterase enzyme. 55 Treatments of the Alzheimer's disease include disease-modifying treatments, psychotropic agents and especially the cholinesterase inhibitors, which block the hydrolysis of two chemical neurotransmitters, i.e., acetylcholine and butyrylcholine (by butylcholineesterase, BChE). 52 However, most of these drugs have side effects such as liver damage and bradycardia.…”
Section: Anticholinesterase Activitymentioning
confidence: 99%
“…Synthetic antioxidants also caused liver damage and carcinogenesis in rats, that stimulated scientists to find new natural and harmless antioxidants, as well as anticholinesterase compounds. 55 Figure 5 shows the effects of PEA or PEB (10 mg/mL) on anticholinesterase activity at different incubation times (5 to 30 min). Remarkably, time-dependent inhibition of butyrylcholinesterase was observed after PEA and PEB treatments.…”
Section: Anticholinesterase Activitymentioning
confidence: 99%